Effect of Translucency and Opacity of Fiber Reinforced Intracanal Posts on Fracture Resistance of Compromised Teeth - Mohammad Reza Maleki Pour; Farzaneh Shirani; Nasrin Rafieian Koopaei (Islamic Dental Association of Iran, 2014)
Background and Aim: Severely damaged teeth with no support at the coronal portion of root canal are very difficult to restore. The aim of this in-vitro study was to evaluate intraradicular reinforcement by dual cure composite resin and two different types of fiber reinforced composite (FRC) posts (translucent and opaque) in structurally compromised roots. Materials and Methods: Root canal therapy was performed for 48 maxillary central inci-sors. The teeth were divided into four groups, and specimens from three groups were pre-pared to simulate the teeth with flared canals. In the 1st group, no weakening was done. In the 2nd group, the compromised area of the root canal was filled with gutta percha. In the 3rd and 4th groups, universal DT light and DT white posts were used respectively in the root canal to 8 mm below the margin of the palatal wall. The posts were cemented with dual-cure composite. In all groups, the access cavity was restored with light-cure compo-site resin. After being mounted, all specimens were pressed at an angle of 45º relative to the long axis of the teeth. The amount of force at fracture was recorded. Results of frac-ture load were evaluated by one-way ANOVA and LSD post hoc test and the results of mode of fracture were evaluated by chi-square test. Results: The mean fracture load for the four groups was 170.12, 71.40, 125.8 and 148.59 kgf, respectively. There was a significant difference between the mean fracture load of 1st and 2nd groups and that of other groups (p=0.001). The mean fracture load of the 4th group was significantly (p=0.002) higher than that of the 3rd group. The frequency of restorable fractures was significantly different between these two groups (p<0.001). Conclusion: Using dual cure composite resin and FRC posts in roots with thin walls will reinforce the compromised teeth but the type of post will affect the outcome.